دور الشعر والأدب في وسائل الإعلام قديماً وحديثاً: ROLE OF POETRY AND LITERATURE IN MEDIA PAST AND PRESENT - Dr. Muhammad Javed (International Research Journal of Arabic and Islamic Studies, 2025)
Poetry and literature play a fundamental role in shaping culture and national identity across the ages. Their influence is not limited to literature and art but extends to media, politics and education. Since ancient times, poetry has been important in the media. It served as a means of expressing opinions and conveying news. It has also played a major role in shaping collective awareness and political and social participation in the Arab world. In the modern era, the role of poetry and literature in the media has changed. This change is due to the development of media, from traditional journalism to electronic and social media. This article focuses on the role of Arabic poetry and literature in the media, both ancient and modern. It explains their influence and the changes in their role over time.